Psychosocial Rehabilitation Program Development for Schizophrenia Patients with an Amphetamine Use Disorder - พลไพรินทร์ ศุกภนิตย์; สว่างวงศ์สิน ศิริลักษณ์; รักษาทรัพย์ ศศินันท์ (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this research was to study the development of a psychosocial rehabilitation program for patients withSchizophrenia and an amphetamine use disorder, and then to study the results using quasi-experimental designs. Five steps were utilized to develop the program: 1)analysis of the problems; 2) planning; 3) prototype; 4) test and improve the program; and 5) a training program. The program had design as a series of eightactivities that were compared using a pretest–posttest experiment. The dependent variables were social functioning, quality of life, re-admit and a return to using drugs; which was tested using twenty person samples. The measuring instruments were social functioning assessment, quality of life assessment, along with follow-up after treatment. The results showed that the two groups’ quality of life and social functioning score increased immediately after treatment, and also after one and three months of treatment. However, the social functioning score of the experimental group was higher than the control group’s score. In addition, after threemonths the experimental group’s numbers for not returning to drug use was higher than those for the control group. Moreover, the control group’s return for inpatient treatment was significantly higher; at a statistical level of .05